2021
DOI: 10.11594/jtls.11.03.06
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Laboratory Features of COVID-19 in Ulin Referral Hospital of South Kalimantan: Predictors of Clinical Outcome

Abstract: Corona Virus Disease (COVID-19) is becoming a global pandemic. Indonesia, especially South Kalimantan had recorded increasing cases with a high fatality rate of 3.7%. Information about factors related to outcomes based on clinical and laboratory features in Indonesia is still limited. Identification of the risk is crucial to determine optimal management and reducing mortality. This retrospective study enrolled 455 adults COVID-19 patients, and data were extracted from medical records of Ulin General Hospital B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The results of this study are similar to previous studies conducted at RSUD Ulin regarding the clinical and laboratory features of confirmed COVID-19 patients treated at RSUD Ulin by Haryati., et al, in the form of significant differences between age and gender in patient outcomes. 18 However, in this study, it was found that comorbidities also had a significant difference between the outcomes of patients who survived versus those who did not. This could be due to the heterogeneity of the wider sample due to the larger number of samples compared to previous studies.…”
Section: Characteristics Of the Study Sample Of Confirmed Covid-19 Pa...mentioning
confidence: 51%
See 2 more Smart Citations
“…The results of this study are similar to previous studies conducted at RSUD Ulin regarding the clinical and laboratory features of confirmed COVID-19 patients treated at RSUD Ulin by Haryati., et al, in the form of significant differences between age and gender in patient outcomes. 18 However, in this study, it was found that comorbidities also had a significant difference between the outcomes of patients who survived versus those who did not. This could be due to the heterogeneity of the wider sample due to the larger number of samples compared to previous studies.…”
Section: Characteristics Of the Study Sample Of Confirmed Covid-19 Pa...mentioning
confidence: 51%
“…Women are thought to be more capable of fighting viruses because of the protection of the X chromosome and sex hormones (estrogens) which play an important role in innate and adaptive immunity. [18][19][20] COVID-19 infection is also more likely to have an adverse outcome in patients with preexisting comorbidities than those without comorbidities. Shi., et al reported that the risk of death in COVID-19 patients with any comorbidities was 2.85 times higher than in the group without comorbidities.…”
Section: Characteristics Of the Study Sample Of Confirmed Covid-19 Pa...mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Other parameters, like inflammation markers, have also been used as predictors for prognosis. 3 These variables complement each other. Based on those considerations, this study aimed to examine their connection and to find their correlation.…”
Section: Introductionmentioning
confidence: 97%
“…1,2 There were 4,260,677 confirmed COVID-19 patients in Indonesia between March 2, 2020 and December 20, 2021, with 144,013 deaths. 2 COVID-19 infection is caused by viruses that enter cells and increase oxygen consumption, causing hypoxia in the cells, which causes oxidative stress and increased activity of antioxidant enzymes like peroxidase, catalase, and superoxide dismutase. Furthermore, oxidative stress can activate a number of transcription factors, including nuclear factor kappa-B (NF κB), p53, HIF-hypoxia-inducible factor 1α, peroxisome proliferator-activated receptor γ (PPAR-γ), β-catenin/Wnt, and Nrf2.…”
mentioning
confidence: 99%